TREATMENT OF IgG4-RELATED DISEASE - E. V. Sokol; V. I. Vasilyev (Научно-практическая ревматология)
IgG4-related disease (IgG4-RD) is a fibroinflammatory condition characterized by the occurrence of tumor-like foci in different organs with a unique histological pattern (moirо-like fibrosis, obvious lymphoplasmacytic infiltration with large numbers of IgG4+ plasma cells, and obliterating phlebitis) and elevated serum IgG4 levels in the majority of patients. Its first-line therapy is glucocorticoids at a starting dose of 0.6 mg/kg/day (equivalent to prednisolone); however, this treatment entails a great number of adverse events and high recurrence rates. The paper provides a review of today's literature on the treatment of IgG4-RD; particular emphasis is laid on the description of therapy with glucocorticoids and rituximab.